Sustainable, resilient, regenerative? The potential of Melbourne’s peri-urban region - Butt, Andrew (Frontiers in Sustainable Cities, 2024)
Peri-urban regions offer significant contributions to city regions as landscapes of food production, resources for urban consumption, as well as for biodiversity and nature conservation – a key part of a city region as a socio-ecological, not simply a socioeconomic, space. Consequently, these roles have long been recognized as crucial to objectives of urban sustainability. They are also sites of socio-ecological tensions that relate to urbanization, as well as to the risk or hazard profile of locations undergoing social change. Whether sustainability, or resilience, in socio-ecological systems is a sufficient goal is increasingly under question. Seeking regenerative city regions, and in particular peri-urban landscapes requires reconsiderations of the relationships between policy, and the practices of communities and the state. Particularly with regard to planning policy this suggests consideration of the city and peri-urban region as connected, but also recognizing the specific qualities and vulnerabilities of peri-urban regions. Using the case of Narrm-Melbourne, Australia where several decades of planning policy have sought outcomes that reflect sustainability objectives this paper concludes that the peri-urban region has a strong potential to offer possibilities for a transformation to a sustainable, and potentially regenerative city region, but that current policy approaches are inadequate as they increase the vulnerabilities of communities, and neglect the potential of planning for multifunctionality and socio-ecological objectives.